Current Landscape and Open Questions on Adjuvant Therapies in Melanoma - Vincenzo De Falco; Stefania Napolitano; Luigi Pio Guerrera; Teresa Troiani (Dermatology Practical & Conceptual, 2021)
Melanoma is a form of skin cancer that is frequently diagnosed at early stages. In most cases, surgical resection is curative. In case of thicker melanomas (> pT1b) without clinical or instrumental evidence of metastasis, a sentinel lymph node biopsy is recommended for staging purposes. If the lymph nodes are the only site of disease (macroscopic or microscopic> 1mm), configuring stage III, the international guidelines recommend the use of adjuvant therapy with checkpoint inhibitors (nivolumab or pembrolizumab) or targeted therapies (dabrafenib plus trametinib). These drugs have shown a significant increase in recurrence-free survival, although some doubts and open questions remain. Specifically, none of the available treatments has shown a clear benefit in the overall survival rates, the advantages they give in stage IIIA are not well known, and finally there are still no prospective clinical studies identifying the best approach to continue the therapeutic process in case of relapse. Furthermore, there are new opportunities opening up with the upcoming results of the neoadjuvant trials that could revolutionize the treatment of clinically evident stage III melanoma.